Psychosocial Risk Factors for Postoperative Pain in Ankle and Hindfoot Reconstruction. (October 2016) - Mulligan, Ryan P.; McCarthy, Kevin J.; Grear, Benjamin J.; Richardson, David R.; Ishikawa, Susan N.; Murphy, G. Andrew
Background: The purpose of this study was to examine factors associated with pain after elective ankle and hindfoot reconstruction. Methods: Patients who underwent major ankle or hindfoot reconstruction over a 3-year period were identified. Retrospective chart review determined patient demographics, comorbidities, surgeries, tobacco, alcohol, and narcotic use, chronic pain, and mood disorders. Primary outcomes were cumulative amount of narcotic prescribed (morphine milligram equivalent dose) in the initial 90-day postoperative period, beyond 90 days, and visual analog pain score (VAS) at a minimum of 1-year follow-up. One hundred thirty-two patients (139 operations) met the inclusion criteria. Results: The average narcotic amount prescribed in the initial 90 days after surgery was 1711 mg (morphine equivalent), and narcotic prescriptions were required after 52 surgeries (35%) past 90 days. Preoperative narcotic use ( P < .01), chronic pain disorder ( P = .02), and mood disorder ( P < .01) were significant risk factors for continued narcotic use past 90 days. Tobacco use ( P = .01) and chronic pain disorder ( P < .01) also were significant risk factors for increased initial postoperative narcotic use. The average VAS score in 91 patients at an average of 2.7-year follow-up was 2.1. Mood disorder was a risk factor for increased VAS ( P < .01). No other associations were noted. Conclusion: Patients being treated for chronic pain, diagnosed with a mood disorder, taking any amount of narcotics preoperatively, or using tobacco products had a statistically significant increased risk for pain postoperatively. The presence of risk factors should prompt physicians to discuss pain management strategies before surgery. Level of Evidence: Level III, comparative series.